Immune Effect of Viable and Heat Killed Lactobacillus acidophilus in Mice Infected with Salmonella typhimurium - Zedan, Zahraa K (Al-Nahrain Journal of Science, 2012)
This study was designed to evaluate the immunological effect of viable and heat killed Lactobacillus acidophilus in mice infected with Salmonella typhimurium. The immunological parameters were total and absolute counts of leucocytes and phagocytic index of peritoneal cells. Twelve mice were divided into four groups. Each group consists of 3 mice. Group 1 was used as a negative control. Group 2 was infected with Salmonella typhimurium and use as positive control. Group 3 was fed with viable Lactobacillus acidophilus culture, and infected with culture of Salmonella typhimurium. Group4 was fed with heat killed Lactobacillus acidophilus culture, and infected with Salmonella typhimurium. Results indicated that treatment mice with viable Lactobacillus acidophilus were effective in enhancing the immune responses against Salmonella typhimurium as compared to negative (distilled water) and positive (Salmonella typhimurium) controls. While, mice fed with heat killed Lactobacillus acidophilus showed no enhancing immune effect on mice infected with Salmonella typhimurium.